Pembalikan Beban Pembuktian dalam Sengketa Harta Bersama di Pengadilan Agama Palopo: Pendekatan Teori Pembuktian Hukum - Bahri, Syamsul; Mustaming, Mustaming; Arif, Firman Muh (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Marriage is a spiritual and physical bond aimed at establishing a harmonious, loving, and compassionate family. However, in reality, divorce is often inevitable and carries far-reaching legal consequences, particularly regarding the ex-wife's financial rights, such as iddah (wajib) maintenance and mut'ah (wajib) maintenance. Although regulations stipulate the husband's obligations after a divorce, in practice, the fulfillment of these rights often faces obstacles, particularly in divorce cases. This phenomenon raises the urgency of reviewing the effectiveness of legal protection for women and children after a divorce to prevent economic neglect. This study aims to analyze the application of the principle of reversal of the burden of proof (omkering van de bewijslast) in resolving joint property disputes at the Palopo Religious Court, identify the obstacles encountered, and review this practice based on legal evidentiary theory. The research method used is empirical juridical with a case study and sociological approach. Data were collected through a study of decision documents from 2020-2024 and interviews with judges and legal practitioners at the Palopo Religious Court. The research findings indicate that the application of the burden of proof in the Palopo Religious Court primarily adheres to the principle of actori incumbit probatio. However, judges apply a reversal of the burden of proof in a case-by-case manner when information asymmetry occurs, where one party (usually the husband) has exclusive access to asset data. This is done to protect the rights of the wife, who is economically vulnerable. The main obstacles to implementing this principle include technical obstacles such as the lack of physical documents, uncooperativeness on the part of the parties, and psychological trauma resulting from the divorce, which hinder the evidentiary process. Furthermore, the lack of a specific Standard Operating Procedure (SOP) makes this practice highly dependent on the judge's discretion and interpretation. Theoretically, this practice aligns with the concept of distributive justice and the values of the maqasid sharia in the protection of property (hifz al-mal) to achieve substantive justice beyond the formalities of procedural law.